VD_FINDINFO Jug / 2021 / 161 vom 19. November 2020 - VD Tribunal cantonal (2020)
VIOLATION DES RÈGLES DE LA CIRCULATION, MAÎTRISE DU VÉHICULE, CONTRAVENTION, PREUVE ILLICITE | 26 LCR, 31 al. 1 LCR, 34 al. 4 LCR, 90 al. 1 LCR